Tangential vitreous traction: a possible mechanism of development of cystoid macular edema in retinitis pigmentosa - Mikiko Takezawa (Dove Medical Press, 2011)
Mikiko Takezawa, Soichi Tetsuka, Akihiro KakehashiDepartment of Ophthalmology, Jichi Medical University, Saitama Medical Center, Saitama, Saitama, JapanAbstract: We report the possible mechanism of development of cystoid macular edema (CME) in retinitis pigmentosa (RP) in the case of a 68-year-old woman with RP and CME in the right eye and resolving CME in the left eye. Spectral domain optical coherence tomography showed CME and posterior vitreoschisis in the nasal quadrant of the fundus without a posterior vitreous detachment (PVD). This vitreous pathology suggested bilateral thickening and shrinkage of the posterior vitreous cortex. In the right eye, CME was evident with no vitreofoveal separation. However, in the left eye, minimal change was seen in the CME associated with a focal shallow PVD over the fovea. The best-corrected visual acuity (BCVA) in the left eye increased to 0.3 from 0.15 7 years after the first visit. Tangential vitreous traction on the macula may have caused the CME in the right eye. The shallow PVD over the fovea might have released the tangential vitreous traction from the fovea, induced spontaneous resolution of the CME, and improved the BCVA in the left eye.Keywords: retinitis pigmentosa, cystoid macular edema, posterior vitreous detachment, posterior vitreoschisis, optical coherence tomography